Human Infrapatellar Fat Pad Mesenchymal Stem Cell-Derived Extracellular Vesicles Inhibit Fibroblast Proliferation by Regulating MT2A to Reduce Knee Arthrofibrosis. (12th April 2023) - Jia, Dazhou; Chen, Hui; Dai, Jihang; He, Shiping; Liu, Yangyang; Liu, Zhendong; Zhang, Yaxin; Li, Xiaolei; Sun, Yu; Wang, Qiang
Abstract : Knee arthrofibrosis is one of the most serious complications of knee surgery; however, its pathogenesis is unclear, and current treatment methods have not achieved satisfactory results. Mesenchymal stem cells (MSCs) have good anti-inflammatory and antifibrotic properties, and studies have reported that human infrapatellar fat pad-derived MSCs (IPFSCs) have the advantages of strong proliferative and differentiating ability, ease of acquisition, and minimal harm to the donor. Increasing evidence has shown that MSCs function through their paracrine extracellular vesicles (EVs). Our study is aimed at exploring the effects of human IPFSC-derived EVs (IPFSC-EVs) on knee arthrofibrosis and the underlying mechanisms in vivo and in vitro. In the in vivo study, injecting IPFSC-EVs into the knee joint cavity effectively reduced surgery-induced knee arthrofibrosis in rats. In the in vitro study, IPFSC-EVs were found to inhibit the proliferation of fibroblasts in the inflammatory environment. Additionally, we screened a potential IPFSC-EV molecular target, metallothionein 2A ( MT2A ), using RNA sequencing. We found that silencing MT2A partially reversed the inhibitory effect of IPFSC-EVs on fibroblast proliferation in the inflammatory environment. In conclusion, IPFSC-EVs inhibit the progression of knee arthrofibrosis by regulating MT2A, which inhibits fibroblast proliferation in the inflammatory environment.